Enterovirus 71 Neutralizing Antibodies Seroepidemiological Research among Children in Guangzhou, China between 2014 and 2015: A Cross-Sectional Study - Dingmei Zhang (International Journal of Environmental Research and Public Health, 2017)
A hand-foot-mouth disease outbreak occurred in 2014 around Guangdong. The purpose of this study was investigating the status and susceptibility of infectious neutralizing antibodies to enterovirus 71 among children so as to provide scientific evidence for the population immunity level of hand-foot-mouth disease and prepare for enterovirus 71 vaccination implementation. Serum specimens were collected from children in communities from January 2014 to March 2015 in Guangzhou. A total of 197 serum samples from children 1–5 years old were collected for this cross-sectional study via non-probabilistic sampling from the database of Chinese National Science and Technique Major Project. Neutralization activity was measured via micro neutralization test in vitro. The positive rate of enterovirus 71 neutralizing antibodies was 59.4%, whereas the geometric mean titre was 1:12.7. A statistically significant difference in true positive rates was found between different age groups but not between different genders. Being the most susceptible population of hand–foot–mouth disease, children under 3 years of age are more likely to be infected with enterovirus 71, and the immunity of children increases with increasing age. Further cohort studies should be conducted, and measures for prevention and vaccination should be taken.